Design and simulation of two-stroke engines - Blair, Gordon P. (Society of Automotive Engineers Warrendale, 1996)
Design and Simulation of Two-Stroke Engines is a unique hands-on information source. The author, having designed and developed many two-stroke engines, offers practical and empirical assistance to the engine designer on many topics ranging from porting layout to combustion chamber profile to tuned exhaust pipes. The information presented extends from the most fundamental theory to pragmatic design, development, and experimental testing issues.
Includes bibliographical references and an index.
Keywords: Two-stroke cycle engines -- Design and construction